Fordham, a history of the Jesuit University of New York : 1841-2003 - Shelley, Thomas J.; Oxford University Press (New York Fordham University Press, 2016)
Based largely on archival sources in the United States and Rome, this volume documents the evolution of Fordham from a small diocesan college into a major American Jesuit and Catholic university. It places the development of Fordham within the context of the massive expansion of Catholic higher education that took place in the United States in the twentieth century.
Online access provided by University Press Scholarship Online.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on December 2, 2016).
Keywords: Fordham University -- History